2015
DOI: 10.1039/c5ce01136a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and spectroscopic studies of luminescentl-valine modified alkynyl-based cyclometalated gold(iii) complexes with gelation properties driven by π–π stacking, hydrogen bonding and hydrophobic–hydrophobic interactions

Abstract: A series of luminescent L-valine modified alkynyl-based cyclometalated goldIJIII) complexes are synthesized and characterized. Through a balance of π-π stacking, hydrogen bonding and hydrophobic-hydrophobic interactions, organogelation of the goldIJIII) complexes is achieved in DMSO. The gelation properties of the complexes have been studied using scanning electron microscopy, transmission electron microscopy, X-ray powder diffraction, variable-temperature NMR, IR, UV-vis absorption and emission spectroscopy. Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…Considering first the complexes with two pincer chains, 16a–18a , they each display vibrationally structured emission spectra in solution at 295 K, in which the 0,0 component is of highest intensity, indicative of high rigidity and little distortion in the excited state compared to the ground state (Figures a and S11). The spectra are typical of the many reported complexes of type 2 , ,,, where the emission is assigned to a metal-perturbed π → π* intraligand transition based on the cyclometallating ligand. Not surprisingly, the λ max values and the spectral profiles are rather similar to those of 16aH – 18aH under the same conditions, just as the absorption spectra were identical, reflecting the “insulation” of the fluorinated chains from the spectroscopically active parts of the molecule.…”
Section: Photophysical Propertiesmentioning
confidence: 77%
See 1 more Smart Citation
“…Considering first the complexes with two pincer chains, 16a–18a , they each display vibrationally structured emission spectra in solution at 295 K, in which the 0,0 component is of highest intensity, indicative of high rigidity and little distortion in the excited state compared to the ground state (Figures a and S11). The spectra are typical of the many reported complexes of type 2 , ,,, where the emission is assigned to a metal-perturbed π → π* intraligand transition based on the cyclometallating ligand. Not surprisingly, the λ max values and the spectral profiles are rather similar to those of 16aH – 18aH under the same conditions, just as the absorption spectra were identical, reflecting the “insulation” of the fluorinated chains from the spectroscopically active parts of the molecule.…”
Section: Photophysical Propertiesmentioning
confidence: 77%
“…More than 15 years ago, Yam and co-workers reported the observation of room-temperature phosphorescence in gold­(III) complexes ligated by a 2,6-diphenylpyridine pincer ligand and a phenyl acetylide (Figure ). A great deal of work has since been published describing many structural variants with impressive results, including high values for both molecular photoluminescence quantum yields (PLQYs) in solution and external quantum efficiencies (EQEs) , for devices employing such complexes as emitters. Further, by using 3,4,5-trialkoxyphenylacetylide co-ligands (=R, Figure ), complexes were realized that showed the ability to gelate .…”
Section: Introductionmentioning
confidence: 99%
“…[12,16] Gold (I) and gold (III) complexes, known for their wide range of applications in catalysis, [17][18][19] optoelectronic materials [20,21] and bioconjugation methodologies, [22][23][24] have been extensively developed due to their unique luminescence properties and aqueous stability. Pioneering amphiphilic molecular design of cyclometalated gold (III) complexes, [25][26][27][28][29] a system, featured with polyethene glycol (PEG), has provided micellar assemblies with good biocompatibility and aqueous solubility in exhibiting activity towards in vitro phototoxicity, reported by Che. [30] In 2018, Besenius and co-workers reported gold (I) metalloamphiphile with a kinetically controlled stepwise nanofibre assembly in buffered aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…[31] Additional weak interactions, e. g. hydrogen bonds, could further promote the aggregation properties of Pt(II) complexes at the condition that a convenient balance takes place between these interactions within the nanostructure. [13] Recent work has been devoted towards the construction of supramolecular assemblies of molecular Pt [32][33][34][35][36][37][38][39][40] or other metal [41][42][43][44] complexes and hydrogenbonding moieties. Yam and co-workers reported that a Lglutamine-derived dialkynylplatinum(II) bipyridine complex aggregated through a combination of hydrogen bonding, πÀ π stacking and Pt•••Pt interactions leading to the formation of a metallogel.…”
Section: Introductionmentioning
confidence: 99%